Boreal Forests: A Global Treasure - United Nations Economic Commission for Europe (United Nations, 2025)
The study offers a comprehensive overview of forests and the forest sector within the boreal biome and delves into the importance of boreal forests in environmental, social, and economic contexts. The study is based on a thorough review of existing literature and data on boreal forests and country-specific national overviews prepared for this project by six UNECE countries with boreal forests. Despite their importance, boreal forests receive less attention than tropical forests. The study addresses this gap, examining their characteristics, management practices, and challenges.